(3CNHGQ Cgd GdbQf GdKGfj YTQ GdgLQi JGQjN GdeeGdjc aj GdbGgQIs
(3ChdgG (B:s
(3hHYO abO SCdJfj CQTOc Gddg Cf CLeY dc LRAkG jTJed Ydi HYV CNHGQ Cgd GdbQf GdKGfj YTQ s
(3BNQgG (B:s
(3Je gPG GdLRA GdeLehY aj CNHGQ (B[(3GdbQf GdKGfj YTQ(B] (3JPcQI dCgd GdHUGFQ eY hLg GdGNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B19 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN WdYJ (B2148) s
Keywords: (3GdJGQjNs